FRC transplantation restores lymph node conduit defects in laminin α4–deficient mice - Lushen Li; Long Wu; Allison Kensiski; Jing Zhao; Marina W. Shirkey; Yang Song; Wenji Piao; Tianshu Zhang; Zhongcheng Mei; Samuel J. Gavzy; Bing Ma; Vikas Saxena; et al. (JCI Insight, 2023)
Fibroblastic reticular cells (FRCs) play important roles in tolerance by producing laminin α4 (Lama4) and altering lymph node (LN) structure and function. The present study revealed the specific roles of extracellular matrix Lama4 in regulating LN conduits using FRC-specific KO mouse strains. FRC-derived Lama4 maintained conduit fiber integrity, as its depletion altered conduit morphology and structure and reduced homeostatic conduit flow. Lama4 regulated the lymphotoxin β receptor (LTβR) pathway, which is critical for conduit and LN integrity. Depleting LTβR in FRCs further reduced conduits and impaired reticular fibers. Lama4 was indispensable for FRC generation and survival, as FRCs lacking Lama4 displayed reduced proliferation but upregulated senescence and apoptosis. During acute immunization, FRC Lama4 deficiency increased antigen flow through conduits. Importantly, adoptive transfer of WT FRCs to FRC Lama4–deficient mice rescued conduit structure, ameliorated Treg and chemokine distribution, and restored transplant allograft acceptance, which were all impaired by FRC Lama4 depletion. Single-cell RNA sequencing analysis of LN stromal cells indicated that the laminin and collagen signaling pathways linked crosstalk among FRC subsets and endothelial cells. This study demonstrated that FRC Lama4 is responsible for maintaining conduits by FRCs and can be harnessed to potentiate FRC-based immunomodulation.